A COMMON VISION FOR A WAY OUT OF THE CYPRUS CONUNDRUM - Sozen, Ahmet (Turkish Policy Quarterly, 2017)
UN-broked peace talks with Cyrpiot leader Nicos Anastasiades and Turkish Cypriot leader Mustafa Akinci have brought the Cyrpus problem once again to the edge of resolution. However, the thorny issue of security and guarantees presents a significant challenge to reaching a deal. The author argues that the key to solving the security and guarantees issue is to start with a common vision that would be agreeable to all relevant parties. This common vision should be based upon establishing the right institutions in the future united federal Cyprus, so that it can have the capacity and the resilience to deal with its security problems without outside assistance. In that regard, it is high time that the two Cypriot leaders earnestly focus on designing those internal security mechanisms and institutions, while the three guarantors should work on the external security and guarantees, and related transitional arrangements.